Grandiflolines A–F, new anti-inflammatory diterpenoid alkaloids isolated from Delphinium grandiflorum - Yan, Yuanfeng; Jiang, Hongjun; Yang, Xiaoyan; Ding, Zongbao; Yin, Tianpeng (Frontiers in Chemistry, 2022)
Delphinium grandiflorum L. (family Ranunculaceae), one of the most important and widely distributed Delphinium species, has received considerable interest due to its extremely high medicinal value. The discovery of novel metabolites from D. grandiflorum supported and broadened its application as an herbal medicine. In this study, the whole herb of D. grandiflorum was phytochemically investigated to obtain fourteen C19-lycaconitine-type diterpenoid alkaloids (1–14), including six undescribed alkaloids, grandiflolines A–F (1–6). The structural elucidation of them was accomplished by detailed spectroscopic analyses, mainly including HR-MS, 1D and 2D NMR (1H-1H COSY, NOESY, HMBC and HSQC), and IR spectra. New alkaloids 1–3 and 5 possess a characteristic △2,3 functional group in the A ring, while compounds 5 and 6 feature a rare OH-16 substituent. In addition, known compounds 7–12 were isolated from D. grandiflorum for the first time. Moreover, according to its medicinal use, new alkaloids 1–6 were estimated for their potential in vitro anti-inflammatory effects, and some of them exhibited inhibitory effects on NO production in LPS-activated RAW 264.7 macrophages. Our work enriched the chemical diversity of D. grandiflorum and the genus Delphinium and presented beneficial information for further investigations.